2014
DOI: 10.1097/meg.0000000000000067
|View full text |Cite
|
Sign up to set email alerts
|

Double-balloon endoscopy

Abstract: Colonoscopy by DBE was useful in most patients in whom conventional colonoscopy was incomplete, irrespective of the cause of the failure. In nearly half the patients, a relevant new diagnosis was made with therapeutic consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…The DBc cecal intubation rate of 95% is comparable to that in other studies, which reported success rates of 88.6%–100% [ 11 , 12 , 17 , 19 - 23 ]. Two of the 3 incomplete DBcs were because of inadequate cleansing of the bowel, which should be avoidable in future to improve intubation rates.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The DBc cecal intubation rate of 95% is comparable to that in other studies, which reported success rates of 88.6%–100% [ 11 , 12 , 17 , 19 - 23 ]. Two of the 3 incomplete DBcs were because of inadequate cleansing of the bowel, which should be avoidable in future to improve intubation rates.…”
Section: Discussionsupporting
confidence: 79%
“…Most studies reported no or few major complications [ 21 - 23 ]. Another Dutch clinical study reported a complication rate of 1.8%, consisting of 2 cases of arterial bleeding [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Balloon-assisted enteroscopes (BAEs), both double balloon as well as single balloon, have shown to be successful as alternative techniques 7 13 14 15 16 17 18 19 20 21 . Manual version of spiral overtube-assisted colonoscopy achieved a cecal intubation rate of 92 % in 24 patients in whom conventional colonoscopy had failed 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Device-assisted colonoscopy with either spiral endoscopy and double or single balloons have identical rates, similar to CCE, of complementing incomplete OC of about 90%[ 28 - 31 ]. These flexible endoscopic techniques additionally provide the possibility to directly treat detected lesions, but they require equipment and expertise, and they are restricted to specialized centres.…”
Section: Discussionmentioning
confidence: 99%